Analysis of Mpox Dynamic Model with Reinfection and Treatment - Chasanah, Siti Laelatul; Nurvazly, Dina Eka; Sandy, Ikhlas Pratama; Hasanah, Arvi (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
This research aims to develop a mathematical model of monkeypox disease spread with reinfection and hospitalization. This model divided the human population into five sub-populations: susceptible, exposed, infectious, hospitalized, and recovered. On the other hand, the animal population is divided into three: susceptible, exposed, and infectious. The results of the model analysis show that the stability of the two equilibrium points, disease-free and endemic, is asymptotically stable when  and , respectively. A sensitivity analysis was conducted on the parameter of the rate at which infected individuals are hospitalized. Based on numerical simulations, a disease-free state has been achieved when more than 68.87% of infected individuals receive hospital treatment. Hospital treatment has a positive impact on efforts to reduce the number of infected individuals in the population. The more individuals who are hospitalized, the greater the number of individuals who are exposed, hospitalized, and recover will increase.